Using Digital Media in Teaching and Learning by English Teachers at Secondary School in Luang Prabang Capital Municipality, Luang Prabang Province - KHAMMELEESAYSUE, Her; PHAIGNAVONG, Somchay; PANFONGPHET, Sipaseuth; ONSENGTAVANH, Fongmany; VANDALAK, Phonesavanh (Souphanouvong University Journal Multidisciplinary Research and Development, 2026)
This is a quantitative research study that aims to investigate the use of digital media in teaching and learning by English teachers at secondary schools in Luang Prabang, Capital Municipality, Luang Prabang Province. The target group for this research consisted of 64 participants selected through simple random sampling. The data collection tool used to gather information about the use of digital media in teaching and learning by English teachers at secondary schools in Luang Prabang Capital Municipality, Luang Prabang Province, was a 5-point rating scale questionnaire. The data were analyzed by using descriptive statistics to determine the mean () and standard deviation (S.D). The overall research findings revealed that the use of digital media in teaching and learning by secondary school English teachers in Luang Prabang Municipality, Luang Prabang Province, was at a moderate level (=3.48; S.D= 0.51). Specifically, it was found that the aspect of access to digital tools in teaching and learning was at a high level (=3.66; S.D= 0.55), the aspect of teaching and learning that emphasizes self-directed knowledge seeking by learners through digital media was at a moderate level (=3.45; S.D= 0.52), the aspect of designing the use of digital media in teaching and learning was at a moderate level (=3.43; S.D= 0.69), the aspect with the lowest usage was the process of teaching and learning through digital media, with a mean value of (=3.39; S.D= 0.60).